Recording the direct surgeon’s view with an operating microscopic view improves microscopic ophthalmic surgery training - Masayuki Akimoto; Kosei Tomita; Miyo Yoshida; Yuki Hama (International Journal of Ophthalmology, 2023)
AIM: To establish a recording system with a direct view of the surgeon to supplement video recording under an operating microscope, which lacks information on the movement and position of the surgeon's hands, and to facilitate the reproduction of a skilled surgeon's technique by a surgeon in training. METHODS: A small camera was attached to the operating microscope with a custom adapter. Microscopic surgeon's view and direct surgeon's view through this new camera were recorded in the surgical recording system. Both movies were synchronized and analyzed how do surgeons handle the instruments. RESULTS: A small camera attached to the operating microscope allowed the surgeon's hands motion to be recorded without interfering with the surgeon's movements. Different surgeons used different methods to manipulate the ultrasound handpiece and the irrigation/aspiration device. Even in the simple paracentesis procedure, different surgeons used different methods. Surgeons-in-training were able to identify and improve their weaknesses by watching synchronized movies of their hand motions and microscopic view. CONCLUSION: Simultaneous recording the surgical field out of the operating microscopic view by a small camera set on the microscope is comprehensive and improves surgeons-in-training understanding and learning surgeries.